Local Governance without Capacity Building Ten Years of Panchayati Raj - D NARAYANA (Economic and Political Weekly June 25, 2005, 2005)
With the passing of the 73rd and 74th constitutional amendments in India the structure of governance has changed permanently from a two-tier to a three-tier system with union, state and panchayats/nagar palikas. However, a necessary condition for the transformation of panchayats into local governments is devolution of powers, resources and functions to them and capacity building among the elected representatives. This paper analyses the functioning of the elected representatives at the gram panchayat level in Madhya Pradesh, Tamil Nadu and Kerala. In Madhya Pradesh and Tamil Nadu, elected ward members show poor awareness of powers and responsibilities, but Kerala is different. In Madhya Pradesh and Tamil Nadu, panchayats are perceived as agents of state governments, whereas in Kerala they are taken as local governments. In all three states, panchayat presidents understand the legislation better but planning for development is a far cry as little effort seems to have gone into capacity building and devolution of powers and resources. Unless larger powers and resources are devolved and elected representatives are trained, local government will be a dream.